Busca à "primeira grandeza" : o Espírito Santo e o governo Moniz Freire (1892 a 1896) - Ribeiro, Diones Augusto (2008)
This research was developed aimed to comprehend the first Moniz Freire government in Espírito Santo, from 1892 to 1896. Having this in mind, we focus on analyzing the main political projects from his govern, mostly the immigration, the railways construction and the urban improvements that had done in Vitória city where we had a great highlight in its project, because the capital of Espírito Santo would channel in its port, the Capixaba coffee production. Our demands are not restricted only to documentary analysis nor search history. Our goal was also to praise someone who has immeasurable importance in the State’s development, in the early years of the Republic. In addiction, contributing to the wealth field of political History and economic future, providing subsidies for those who, as ourselves, look after along the History recovering from Espírito Santo and Brazil as well.